Microbial eukaryotic distributions and diversity patterns in a deep‐sea methane seep ecosystem. (25th January 2016) - Pasulka, Alexis L.; Levin, Lisa A.; Steele, Josh A.; Case, David H.; Landry, Michael R.; Orphan, Victoria J.
Summary: Although chemosynthetic ecosystems are known to support diverse assemblages of microorganisms, the ecological and environmental factors that structure microbial eukaryotes (heterotrophic protists and fungi) are poorly characterized. In this study, we examined the geographic, geochemical and ecological factors that influence microbial eukaryotic composition and distribution patterns within Hydrate Ridge, a methane seep ecosystem off the coast of Oregon using a combination of high‐throughput 18S rRNA tag sequencing, terminal restriction fragment length polymorphism fingerprinting, and cloning and sequencing of full‐length 18S rRNA genes. Microbial eukaryotic composition and diversity varied as a function of substrate (carbonate versus sediment), activity (low activity versus active seep sites), sulfide concentration, and region (North versus South Hydrate Ridge). Sulfide concentration was correlated with changes in microbial eukaryotic composition and richness. This work also revealed the influence of oxygen content in the overlying water column and water depth on microbial eukaryotic composition and diversity, and identified distinct patterns from those previously observed for bacteria, archaea and macrofauna in methane seep ecosystems. Characterizing the structure of microbial eukaryotic communities in response to environmental variability is a key step towards understanding if and how microbial eukaryotes influence seep ecosystem structure and function.